Oxford English for electrical and mechanical engineering - Glendinning, Eric H (Oxford University Press, 2001)
The book consists of thirty units which contain authentic reading and listening passages from a wide variety of sources. Te topics have been chosen to cover areas that are common to both electrical engineering and mechanical engineering